2015
DOI: 10.1002/sca.21196
|View full text |Cite
|
Sign up to set email alerts
|

Leucine‐rich amelogenin peptide (LRAP) as a surface primer for biomimetic remineralization of superficial enamel defects: An in vitro study

Abstract: This study was carried out to obtain more information about the assembly of hydroxyapatite bundles formed in the presence of Leucine-Rich Amelogenin Peptide (LRAP) and to evaluate its effect on the remineralization of enamel defects through a biomimetic approach. One or 2 mg/mL LRAP solutions containing 2.5 mM of Ca(+2) and 1.5 mM phosphate were prepared (pH = 7.2) and stored at 37 °C for 24 h. The products of the reaction were studied using atomic force microscopy (AFM), transmission electron microscopy (TEM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 45 publications
4
31
0
Order By: Relevance
“…16,21,22 Although previous studies suggested that LRAP is a HAP crystal growth inhibitor, 15 current studies indicate that it may have an important function in promoting enamel mineralization. 23,24 Several other functions have also been attributed to LRAP in vivo, including that of a cell-signaling molecule capable of inducing osteogenesis in different cell types such as mouse cementoblasts 25 and embryonic stem cells. 26 In this in vitro study, phosphorylated human LRAP was added to a chitosan hydrogel (LRAP-CS) to determine whether it could promote aligned crystal growth for biomimetic repair as effectively as the full-length amelogenin (rP172) in minimal treatment time.…”
Section: Introductionmentioning
confidence: 98%
“…16,21,22 Although previous studies suggested that LRAP is a HAP crystal growth inhibitor, 15 current studies indicate that it may have an important function in promoting enamel mineralization. 23,24 Several other functions have also been attributed to LRAP in vivo, including that of a cell-signaling molecule capable of inducing osteogenesis in different cell types such as mouse cementoblasts 25 and embryonic stem cells. 26 In this in vitro study, phosphorylated human LRAP was added to a chitosan hydrogel (LRAP-CS) to determine whether it could promote aligned crystal growth for biomimetic repair as effectively as the full-length amelogenin (rP172) in minimal treatment time.…”
Section: Introductionmentioning
confidence: 98%
“…The non-phosphorylated leucine-rich amelogenin peptide contains only the N-and C-terminal domains of the parent amelogenin, with these domains known to be responsible for directing mineral growth and binding [Le Norcy et al, 2011]. In vitro studies have shown treatment of enamel lesions with leucine-rich amelogenin peptide reduced lesion depth and allowed biomimetic reconstruction of enamel by promoting linear growth of mature enamel crystals along the c-axis [Bagheri et al, 2015;Mukherjee et al, 2016;Shafiei et al, 2015]. The addition of mineralization inhibitors such as inorganic pyrophosphate or matrix metalloproteinase to synthetic amelogenin assemblies was able to better regulate size, shape, and orientation of a strongly adherent new mineral layer, while preventing undesirable protein occlusion within newly formed crystals [Kwak et al, 2017;Prajapati et al, 2018].…”
Section: Amelogeninmentioning
confidence: 99%
“…For example, the leucine-rich amelogenin peptide (LRAP), was proved having striking similarities with full-length amelogenin in respects of self-assembly and protein-mineral interaction (Le Norcy et al, 2011). Not recently, it was reported that LRAP is able to enhance the remineralization of the acid-etched enamel (Shafiei et al, 2015), justifying our speculation that sequence of amelogenin might well have the potential to functional positively in enamel biomimetic remineralization. In this study after treated with this peptide, the surface microhardness and mineral content of the enamel lesion were significantly improved than demineralized enamel and at the same time the lesion depth also become much more shallower, all these results domenstrating that this peptide, which is based on amelogenin Gln-Pro-X sequence has a positively enhancing remineralization effect.…”
Section: Discussionmentioning
confidence: 90%
“…However, during enamel maturation, amelogenin is degraded, and the resulting peptides remain in the diffusion channels of mature enamel, where they may affect the re/demineralization equilibrium (Brookes, Robinson, Kirkham, & Bonass, 1995b). What is more, studies have identified key amino acids in amelogenin sequence that are particularly important for crystal growth, raising the possibility that peptides containing those key residues may be effective in enamel biomimetic remineralization (Du, Falini, Fermani, Abbott, & Moradian-Oldak, 2005;Shafiei et al, 2015).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation